Auxin producing non‐heterocystous Cyanobacteria and their impact on the growth and endogenous auxin homeostasis of wheat. (14th June 2013) - Mazhar, Sumaira; Cohen, Jerry D.; Hasnain, Shahida
<x xml:space="preserve">Abstract</x> Four non‐heterocystous cyanobacterial strains isolated from rhizosphere and soil surface mat of rice, wheat, and maize were identified by 16S rRNA gene sequencing and evaluated for auxin production as well as growth promotion of wheat. Isolated strains produced a diverse amount of auxin in BG11 media supplemented with different concentrations of L‐tryptophan. The amount of auxin detected with colorimetric methods was higher as compared to GC–MS analysis. Auxin production by cyanobacterial strains in BG 11 medium supplemented with 250 µg ml−1L‐tryptophan ranged from 0.20 to 1.63 µg ml−1 IAA as revealed by gas chromatography and mass spectrometric (GC–MS) analysis. In a hydroponic growth system, the vegetative growth of wheat was stimulated appreciably by inoculation with cyanobacterial strains. The endogenous auxin content of wheat was significantly correlated with the exogenous auxin production of the cyanobacterial strains. It was observed that cyanobacterial strains produced more endogenous and exogenous auxin in the presence of a plant, showing that plants might be releasing some signals responsible for higher auxin production by cyanobacterial cultures. It was concluded that the auxin producing potential of cyanobacterial strains can be exploited for the promotion of wheat growth.